2022
DOI: 10.1021/acssuschemeng.1c06315
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Linear Alcohols in Amorphous Activated Carbons: Implications for Energy Storage Applications

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 91 publications
(176 reference statements)
1
12
0
Order By: Relevance
“…Our previous publication investigated the adsorption-driven heat transfer of the four first aliphatic alcohols for heat storage applications using activated carbons. 58 We concluded that methanol exhibits the best performance among the other alcohols for heat storage applications in large pore nanoporous materials. We analyzed the effect of the hydrophobic/hydrophilic nature of the adsorbent on the adsorption behavior, external operating conditions, and energy storage.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Our previous publication investigated the adsorption-driven heat transfer of the four first aliphatic alcohols for heat storage applications using activated carbons. 58 We concluded that methanol exhibits the best performance among the other alcohols for heat storage applications in large pore nanoporous materials. We analyzed the effect of the hydrophobic/hydrophilic nature of the adsorbent on the adsorption behavior, external operating conditions, and energy storage.…”
Section: Introductionmentioning
confidence: 84%
“…This theory is based on the idea that the adsorption mechanisms in micropores is due to the volume filling by the gas molecules instead of surface coverage by successive adsorbed layers . A brief description of the thermodynamical model as used in this work can be found in the Supporting Information and is also available in the literature. ,,,,, In short, we first used the adsorption isobars and isotherms to calculate the adsorption characteristic curve . This reduces the two-dimensional relation between loading ( q ( p , T )), temperature ( T ), and pressure ( p ), to the temperature–pressure invariant characteristic curve ( W ( A )).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations